The The Overview of Shivering and Blood Preassure Occurance Before and After Liquid Co-Loading on Sectio Caesarea Patients: English - Fatmawati, Anisa; Mixrova Sebayang, Septian; Yunida Triana, Noor; Suandika, Made (Global Indonesia Health Care (GOICARE), 2023)
Background: The incidence of shivering and hypotension in cesarean delivery is frequent. The incidence of shivering due to spinal anesthesia is reported to reach 50-65%. While hypotension after spinal anesthesia in sectio caesarea can occur up to 80%. Fluid coloading is done to reduce shivering and overcome hypotension in mothers who have cesarean delivery. Purpose: the study was to determine the description of the incidence of shivering and blood pressure before and after fluid coloading in sectio caesarea patients at RSI Banjarnegara. Method: The design of this study was descriptive with a cross-sectional approach. The study was conducted in June 2023. The sample of this study was 44 respondents with purposive sampling techniques. Results: The showed that the incidence of shivering was experienced by many respondents after being given coloading, which was 37 respondents (84.1%) compared to before coloading there were only 5 respondents (11.4%). While in blood pressure, before coloading the majority experienced hypotension events as many as 37 respondents (84.1%) and after coloading most of the blood pressure became normal as many as 41 respondents (93.2%). Conclusions: It can be concluded that fluid coloading is less effective for shivering treatment, but fluid coloading is effective in maintaining blood pressure in mothers undergoing sectio caesarea after spinal anesthesia.